Hazārah qabāʼil Pākistān men̲ : (taḥrīrī shahādāt kī farāhamī) - ʻAlī, Ṣādiq, 1944-; Beg, Jamshīd; Tanẓīm-i Nasl-i Nau Hazārah Mug̲h̲ul (Quetta, Pakistan). Akādamī Hazāragī. (Koʼiṭah : Hazāragī Ikaiḍamī, Tanz̤īm-i Nasl-i Nau Hazārah Mug̲h̲ul, 2017)
Hisotrical study of Hazāras tribe; includes
On the history and social conditions of Hazāras in Pakistan.
In Urdu.
Keywords: Hazāras -- Pakistan -- Balochistān -- History; Hazāras -- Pakistan -- Balochistān -- Social conditions; Hazāras.; Pakistan -- Balochistān.; History